THE INFLUENCE OF WORKLOAD AND WORK ENVIRONMENT ON THE PERFORMANCE OF 25 KORAMIL SERVICES IN PASURUAN CITY - Junita Rosalia P; Yufenti Oktafiah; Hari Wahyuni (Universitas Islam Lamongan, 2023)
In the era of globalization, company competition is getting higher and more complex so that companies/agencies are required to improve matters related to each company and be more responsive in order to continue to survive and continue to grow. This study aims to determine the effect of workload and work environment on the performance of Koramil 25 soldiers in Pasuruan City. The population used was Babinsa Koramil 25 Pasuruan City using the census method because all soldiers were sampled and only 42 respondents were Koramil soldiers in Pasuruan City. The analysis used is Multiple Linear Regression. The results of this study indicate that: Workload and work environment affect the performance of Koramil 25 soldiers in Pasuruan City. This can be seen based on the results of the F test with a sig. 0.000 < 0.05. The coefficient of determination (R2) or the simultaneous contribution of workload and work environment to the performance of Koramil 25 Soldiers in Pasuruan City is48.3%, while the rest is influenced by other variables outside of this study such as working hours and work facilities.